Implementasi Regresi Linier Berganda Untuk Prediksi Jumlah Peminat Mata Kuliah Pilihan - Nur Kholida Afkarina; Agus Wahyu Widodo; Muhammad Tanzil Furqon (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Higher education is a continuation of education at a higher level after completing secondary education. With so many elective courses with each interest, it makes students have difficulty in knowing the number of interested ones. To overcome the problems that exist, this study predicts the number of interested subjects with multiple linear regression methods. Therefore we need a system to predict the number of interested subjects. There are two features used, namely the average student score in the previous year, the number of interested ones in the previous year. The method used is multiple linear regression. The training data used to determine the number of interested parties in taking courses is the 2013-2017 student data. As for the test data using student data for 2018-2019. From this research, the predicted MAPE score of Fuzzy Logic (2017) is 61.52% and in 2016 is 49.64%